Management of pregnancy in women with monogenic diabetes due to mutations in GCK, HNF1A and HNF4A genes - Crowley, M. T.; Paponette, B.; Bacon, S.; Byrne, M. M. (Frontiers in Genetics, 2024)
Women with maturity-onset diabetes of the young (MODY) need tailored antenatal care and monitoring of their offspring. Each MODY subtype has implications for glycaemic targets, treatment choices and neonatal management. Hyperglycaemia of MODY is often first diagnosed in adolescence or early adulthood and therefore is clinically relevant to pregnant women. Pregnancy represents an opportune time to make a genetic diagnosis of MODY and provide precision treatment. This review describes the nuance of antenatal care in women with MODY and the implications for pregnancies affected by paternal carrier positivity. Mutations in hepatic nuclear factor 1-alpha (HNF1A) and 4-alpha (HNF4A) genes are associated with progressive -cell dysfunction resulting in early onset diabetes. Patients are largely managed with sulphonylureas outside of pregnancy. Macrosomia and persistent neonatal hypoglycaemia are reported in 54% and 15% of HNF4A genotype positive offspring respectively with a median increase in birthweight of 790g. Close observation of foetal growth allows optimal timing of delivery to minimise peri- and post-partum complications. Glucokinase (GCK)-MODY causes mild fasting hyperglycaemia which does not require treatment outside of pregnancy. Birthweight of maternal carrier offspring is dependent on foetal genotype; heterozygous mutation carriers are usually normal weight while genotype negative offspring are large for gestational age (600g heavier). Affected paternal carrier offspring may be small for gestational age (500g lighter). Serial measurement of the abdominal circumference indirectly differentiate foetal genotype. Measurement of cell free foetal DNA in maternal blood is superior to traditionally used ultrasound to distinguish foetal genotype. Cost and accessibility may limit its use.